Risks in Islamic banks: evidence from empirical research - Mohd. Ariffin, Noraini; Archer, Simon; Karim, Rifaat Ahmed Abdel (Palgrave Macmillan, 2009)
This study attempts to ascertain the perceptions of Islamic bankers (chief financial officers and risk managers) about the nature of risks, risk measurement and risk management techniques in their banks. It covers 28 Islamic banks in 14 countries using a questionnaire survey. The results indicate that Islamic banks are mostly exposed to similar types of risks to those in conventional banks, but that there are differences in the level of the risks. The findings of the study have both theoretical and policy implications for the issue of transparency, with particular reference to risk reporting in Islamic banks.